Analysis of the French Language Learning Multimedia Development in Integrated Islamic Elementary School - Sandy Lesmana; Yumna Rasyid; Sri Harini Ekowati (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
This study aims to describe the problems in the application of French as a language used to communicate in the school environment, the level of active French language skills, and also the level of need for the development of multimedia learning French to further practice speaking skills in French carried out by students in the school environment. This research was a descriptive qualitative research with 60 student needs evaluation questionnaires of French language learning multimedia, interviewed the headmaster, and two French teachers. The sample of this research is the principal, French teacher and also students at SDIT Ar-Raudhah, Bekasi from the third until the sixth grade who were selected using random sampling method. The data was collected by interviewing the principal and also the French teacher. In addition, a questionnaire or open questionnaire was given to students. The data that has been collected is then analyzed using qualitative descriptive techniques. The results of research showed that there was a decline in the practice of speaking French in the school environment caused by various problems faced by students, such as the difficulty of students understanding French material and grammar, lack of confidence from students to communicate using French, there is no firmness from the school on the rules made in improving the ability of students to communicate using French and learning support media that are still incomplete to be used by students in improving their ability to communicate using French. This shows that the level of development need for multimedia in learning French, especially in the aspect of speaking skills is very high, thus requiring schools to be able to provide facilities that use multimedia in the French language learning process at SDIT Ar-Raudhah.